The Effect of Motivational Interviewing on Physical Activity in Subjects with Chronic Obstructive Pulmonary Disease - Kahrmann, Nicolas; Scheermesser, Mandy; Rausch Osthoff, Anne-Kathrin (physioscience, 2019)
Background Current guidelines emphasise the importance of physical activity in the treatment of people with COPD. In general the physical activity level of of people with COPD is lower compared to healthy subjects. Evidence of the effectiveness of counselling in helping people with COPD to increase their activity is inconclusive. The promising method of motivational interviewing (MI) increased the activity levels in people with other chronic diseases.Objective The aim of this review was to examine the effect of MI-based counselling on activity levels in people with COPD.Method A systematic review on studies addressing short-term and preferably long-term effects of MI-based counselling on activity levels in people with COPD was performed in PubMed, CINAHL, PEDro, Cochrane Library, psycINFO and Web of Science. The study quality was assessed using the PEDro scale and the TIDieR checklist.Results The review included seven randomised controlled trials (RCT). Two of the three RCT with clinically relevant between-group differences showed also statistically significant effects.Conclusion MI-counselling might have a positive short-term effect on physical activity in people with COPD. However, all studies showed no long-term impact.
Keywords: chronic obstructive pulmonary disease; COPD; motivational interviewing; physical activity; health counselling; behavioural change